Long-term prognosis and cost-effectiveness of left ventricular assist device as bridge to transplantation: A systematic review. (15th May 2017) - Seco, Michael; Zhao, Dong Fang; Byrom, Michael J.; Wilson, Michael K.; Vallely, Michael P.; Fraser, John F.; Bannon, Paul G.
Abstract: Background: This systematic review aimed to evaluate the clinical outcomes and cost-effectiveness of left ventricular assist devices (LVADs) used as bridge to transplantation (BTT), compared to orthotopic heart transplantation (OHT) without a bridge. Method: Systematic searches were performed in electronic databases with available data extracted from text and digitized figures. Meta-analysis of short and long-term term post-transplantation outcomes was performed with summation of cost-effectiveness analyses. Results: Twenty studies reported clinical outcomes of 4575 patients (1083 LVAD BTT and 3492 OHT). Five studies reported cost-effectiveness data on 837 patients (339 VAD BTT and 498 OHT). There was no difference in long-term post-transplantation survival (HR 1.24, 95% CI 1.00–1.54), acute rejection (HR 1.10, 95% CI 0.93–1.30), or chronic rejection and cardiac allograft vasculopathy (HR 0.99, 95% CI 0.73–1.36). No differences were found in 30-day post-operative mortality (OR 0.91, 95% CI 0.42–2.00), stroke (OR 1.64, 95% CI 0.43–6.27), renal failure (OR 1.43, 95% CI 0.58–3.54), bleeding (OR 1.56, 95% CI 0.78–3.13), or infection (OR 2.44, 95% CI 0.81–7.38). Three of the five studies demonstrated incremental cost-effectiveness ratios below the acceptable maximum threshold. The total cost of VAD BTT ranged from 316, 078 to 1, 025, 500, and OHT ranged from 179, 051 to 802, 200. Conclusion: LVADs used as BTT did not significantly alter post-transplantation long-term survival, rejection, and post-operative morbidity. LVAD BTT may be cost-effective, particularly in medium and high-risk patients with expected prolonged waiting times, renal dysfunction, and young patients.